1995
DOI: 10.1016/s0969-2126(01)00255-6
|View full text |Cite
|
Sign up to set email alerts
|

The three domains of a bacterial sialidase: a β-propeller, an immunoglobulin module and a galactose-binding jelly-roll

Abstract: The presence of the additional carbohydrate-binding domain in the 68 kDa form of the bacterial sialidase reported here is a further example of a combination of carbohydrate binding and cleaving domains which we observed in the sialidase from Vibrio cholerae. This dual function may be common, but only to other bacterial and parasitic sialidases, but also to other secreted glycosidases involved in pathogenesis. The bacterium may have acquired both the immunoglobulin module and the galactose-binding module from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
191
1
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(203 citation statements)
references
References 41 publications
(48 reference statements)
10
191
1
1
Order By: Relevance
“…Previously proposed prokaryotic examples of the IgSF have been recognized on the basis of similar folding topologies, but their sequence similarity to eukaryotic IgSF members has been so low as to raise questions of possible evolution from two independent ancestors (Hofmann et al, 1989; Bork et al, 1994;Gaskell et al, 1995). We have detected these domains based solely on sequence similarities, and thus feel confident drawing a conclusion of divergent evolution.…”
Section: Rhqvtttk-----ykstfeissvqasdegnyswvens-egkq-eaeftltiqmentioning
confidence: 60%
“…Previously proposed prokaryotic examples of the IgSF have been recognized on the basis of similar folding topologies, but their sequence similarity to eukaryotic IgSF members has been so low as to raise questions of possible evolution from two independent ancestors (Hofmann et al, 1989; Bork et al, 1994;Gaskell et al, 1995). We have detected these domains based solely on sequence similarities, and thus feel confident drawing a conclusion of divergent evolution.…”
Section: Rhqvtttk-----ykstfeissvqasdegnyswvens-egkq-eaeftltiqmentioning
confidence: 60%
“…The fold comprises predominantly coil, but does have two small β-sheets and a small region of helix ( Figure 1). This fold can accommodate a surprisingly extended binding site as exemplified by WGA, [52]); (e) family 2 CBM, Cf CBM2, from Cellulomonas fimi (PDB code 1EXG [81]); (f) family 9 CBM, TmCBM9-2, from T. maritima in complex with cellobiose (PDB code 1I82 [33]); (g) family 32 CBM, MvCBM32, from Micromonospora viridifaciens in complex with galactose (PDB code 1EUU [65]); (h) family 5 CBM, EcCBM5, from Erwinia chrysanthemi (PDB code 1AIW [82]); (i) family 13 CBM, SlCBM13, from S. lividans in complex with xylopentaose (PDB code 1MC9 [48]); (j) family 1 CBM, TrCBM1, from Trichoderma reesi (PDB code 1CBH [83]); (k) family 10 CBM, CjCBM10, from Cellvibrio japonicus (PDB code 1E8R [84]); (l) family 18 CBM from Urtica dioca in complex with chitotriose (PDB code 1EN2 [85]); (m) family 14 CBM, tachychitin, from Tachypleus tridentatus (PDB code 1DQC [86]). Bound ligands are shown as 'liquorice' representations, while bound metal ions are shown as a blue spheres.…”
Section: Hevein Foldmentioning
confidence: 99%
“…In general, this family of CBMs is found exclusively in xylanases, and this particular CBM from T. maritima has the remarkable property of recognizing the reducing end sugars of xylans and cellulose. Family 32 is a relatively new CBM family whose only currently (partially) characterized member is the C-terminal module from the Micromonospora viridifaciens sialidase [61,65]. This CBM has a very similar fold to the fucose-specific lectin from Anguilla anguilla and appears to bind galactose [61].…”
Section: Type C Small-sugar-binding Cbmsmentioning
confidence: 99%
“…Active site residues are shown as black on yellow; ''Asp-box'' repeats are shown as black on blue; and novel missense mutations identi¢ed in the human sialidase gene are shown as black on pink. The b-sheets in the structures of bacterial sialidases [Gaskell et al,1995;Crennell et al,1993Crennell et al, ,1994 are indicated by arrows above the alignment.…”
Section: Missense Mutationsmentioning
confidence: 99%